Solvent Evaporation Method and Crystal Structure of 1,3-Dimethyl-3-(2,2,2-trifluoro-ethyl)-1H,3H-1-aza-phenalen-2-one - Zhao, Y.; Zhang, L. (Asian Journal of Chemistry, 2015)
One new compound [N-arylacrylamides (0.30 mmol), PhI(OAc) (0.6 mmol), NaOAc (0.6 mmol) in NMP (1 mL) was added TMSCF3 (1.8 mmol)] has been successfully synthesized. Compound shows a one-dimensional framework. The 1D supramolecular structure is formed via hydrogen bonding connection.